Interaction investigation of three forest waste biochars and CaO in the process of Ca-L/CARBONOx. (1st April 2023) - Li, Jin-gang; Xiong, Zi-ru; Zhang, Li-hui; Duan, Feng
Highlights: Simultaneous CO2 /NO removal experiments using CaO/BCs in CaL/CARBONO x are studied. CO2 /NO removal rate and cyclic removal performance of three biochars are compared. The de-NO x performance of three biochars is related to their pore structure. CaO provides active sites for the adsorption of NO and CO, and lower CO emission. CaO shows a strong catalysis effect on NO reduction by CO produced by biochar oxidation. Abstract: Ca-L/CARBONO x technology has realized the simultaneous removal of CO2 and NO in the flue gas from coal-fired power plants. Forest wastes are characterized by wide sources, low cost, high lignin content, and high chemical activity. In this study, three forest waste biochars including elm biochar (YB), fir biochar (SB) and bamboo biochar (ZB) were blended with CaO, and their simultaneous CO2 /NO removal characteristics were compared. The interaction mechanism between CaO and biochar (BC) in the Ca-L/CARBONO x process was also discussed. Results show that the addition of biochar inhibits the pore structure collapse of CaO at higher cyclic numbers. CaO can also improves the NO removal efficiency for three biochars by catalyzing and providing active adsorption sites. The removal efficiency of NO by three biochars added with CaO are greater than 97% at 650 ℃ in the chemical control stage of CO2 adsorption. SB showed the best NO removal performance and reaction selectivity among the three biochars. Under the presence of CaO, CaO/YB and CaO/ZB have similar CO2 capture performance, while CaO/SB and CaO/ZB have the highest NO removal performance and the best NO reaction selectivity, respectively.